Understanding How Democratic Parenting Style, Single Parent Resilience, School Environment, And Religious Education Influence Child Character Development - Salsabila Andrina; Ranti Karlaili (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
This study aims to investigate the impact of democratic parenting style, single parent resilience, school environment, and religious education on child character development. Through an exploratory approach, the research seeks to understand the intricate interplay between these factors and their effects on shaping children's character traits. The study employs purposive sampling to gather insights from diverse perspectives, including parents, educators, and religious leaders. Data analysis involves thematic coding to identify recurring patterns and themes within the narratives. Initial findings suggest that democratic parenting fosters independence and empathy in children, while single parent resilience contributes to resilience-building. Additionally, the school environment and religious education play significant roles in instilling moral values and ethical principles. These findings underscore the multifaceted nature of child character development and highlight the importance of considering various influences in nurturing well-rounded individuals.